Community Perceptions Related To Covid-19 Vaccination Information In Denai Kelurahan, Medan Denai District, Medan City (International Journal of Cultural and Social Science, 2022)
Polemics related to the effectiveness of vaccinations are still happening today, this makes the community divided between two groups, namely the group who believes that vaccination can minimize cases of COVID-19 and the group who is afraid of the side effects caused by the vaccine due to the large amount of news circulating. among the public about the side effects of the covid-19 vaccine. The purpose of this study was to determine the perceptions and decisions taken by the people of Denai Village, Medan Denai District, Medan City regarding circulating vaccination information. The theory used in this research is Collective Informative Sampling. The research method used is descriptive qualitative. This study found results that the public considered that vaccination was not a guarantee that a person would not be exposed to the corona virus, this was due to personal factors within them, namely the experiences they saw or felt both from the media and directly. People who are afraid of the side effects of vaccination prefer to use the services of making vaccine certificates without having to be vaccinated. Therefore, only 4 of the 11 interviewees had vaccinated, 5 of them preferred to use the service of making a vaccine certificate without having to be vaccinated, the other 3 were not willing to be vaccinated or to use the service of making the vaccine.